Development of 99mTc radiolabeled A85380 derivatives targeting cerebral nicotinic acetylcholine receptor: Novel radiopharmaceutical ligand 99mTc-A-YN-IDA-C4. Issue 18 (15th September 2019) - Mori, Daisuke; Kimura, Hiroyuki; Kawashima, Hidekazu; Yagi, Yusuke; Arimitsu, Kenji; Ono, Masahiro; Saji, Hideo
Graphical abstract: Abstract: Nicotinic acetylcholine receptors (nAChRs) are pentameric ligand-gated ion channels that have been implicated in higher brain functions. To elucidate the functional mechanisms underlying nAChRs and contribute significantly to development of drugs targeting neurological and neuropsychiatric diseases, non-invasive nuclear medical imaging can be used for evaluation. In addition, technetium-99m ( 99m Tc) is a versatile radionuclide used clinically as a tracer in single-photon emission computed tomography. Because A85380 is known as a potent α4β2-nAChR agonist, we prepared A85380 derivatives labeled with 99m Tc using a bifunctional chelate system. A computational scientific approach was used to design the probe efficiently. We used non-radioactive rhenium (Re) for a 99m Tc analog and found that one of the derivatives, Re-A-YN-IDA-C4, exhibited high binding affinity at α4β2-nAChR in both the docking simulation (−19.3 kcal/mol) and binding assay (Ki = 0.4 ± 0.04 nM). Further, 99m Tc-A-YN-IDA-C4 was synthesized using microwaves, and its properties were examined. Consequently, we found that 99m Tc-A-YN-IDA-C4, with a structure optimized by using computational chemistry techniques, maintained affinity and selectivity for nAChR in vitro and possessed efficient characteristics as a nuclear medicine molecular imaging probe, demonstrated usefulness of computational scientific approach for molecular improvement strategy.